Evaluasi Program Praktik Kerja Lapangan (PKL) Pada Kompetensi Keahlian Tata Busana SMK Syubbanul Wathon Tegalrejo: Evaluation of the Field Work Practice Program (PKL) in the Fashion Design Expertise Competency of Syubbanul Wathon Tegalrejo Vocational School - Muwafaqotun Nasichah; Hasyim, Ahmad Fuad; Sari, Dakusta Puspita (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The high unemployment rate of Vocational High School (SMK) graduates in Indonesia, reaching 22% of the total national unemployment, indicates a mismatch between graduate competencies and the needs of the business world and industry (DUDI). To overcome this problem, the Field Work Practice Program (PKL) is designed to strengthen the relationship between education and industry. This study evaluates the implementation of PKL on the Fashion Design Expertise competency of SMK Syubbanul Wathon Tegalrejo, a vocational school based on an Islamic boarding school that implements PKL based on Teaching Factory, using a descriptive qualitative evaluation method with the CIPP (Context, Input, Process, Product) approach. Data were collected through observation and interviews. The evaluation results show that in terms of Context Evaluation, SMK Syubbanul Wathon has adequate facilities and teaching staff to support the implementation of PKL. Input Evaluation shows that PKL planning and preparation are carried out well and in a structured manner, although there are limitations in human resources in the field of Fashion Design. In the Process Evaluation, the implementation of PKL went according to plan, but direct interaction between students and mentors from DUDI was still limited and mostly done online. Product evaluation revealed that some students successfully completed the project on time and showed increased competence, but others were still unable to complete the project on time. In addition, students gained new knowledge about the fashion industry and were satisfied with the internship experience, although improvements were needed in instilling a work culture. Overall, the implementation of the Teaching Factory-based internship with external mentors is still relevant and useful. Recommendations for further research include the development of more effective mentoring methods and continuous assessment of industry needs.